“Return To Babylon” A poem by Ali Jaafar Al-Alaq The poem from Lyrical to Narrative - الساعدي عارف (Al-Adab Journal, 2018)
The poem "Return to Babylon" by the poet Ali Jaafar Al-Alaq has become a phenomenon within which numerous details of a homeland that was consumed and whose dreams where grinded by the wars of his sons and enemies alike. The essential aesthetical question, however, is that how the poetic text can have or endure all these details that are submerged in realism but poetically and aesthetically expressed? making this poem aesthetic documentary of an era that is absolutely unaesthetic. Al-Alaq’s poetic talent is certainly the key factor for this poem to utilize a number of writing techniques, most important of which is narrative in general and biographical in particular, where the narrative aspect of the poem has formed the controlling element that ties the events of the poem together, as it has become the main factor in the frequency and tension of the poem since narrating a biography in a poetic form has two aspects; first: controlling the logical sequence of events, and second: the suspense factor in narrative in spite of the painful events being narrated.